Tax reform of 2025: burden on individuals - N. Z. Zotykov (Вестник университета, 2025)
According to the Russian legislation, taxpayers in Russia are both legal entities and individuals. The subject of the study is taxation of the individuals. The purpose of the article is to analyse changes made to the tax legislation from 2025 (the tax reform of 2025), their impact on the social status of the individuals (on the tax burden). The study uses the following methods: analysis and synthesis, grouping, generalisation, consideration of phenomena in dynamics, tabular method. The information base are changes in taxation from 2025, reports of the Federal Tax Service, official data from the Federal State Statistics Service, internet resources, publications   on the topic under study, etc. The research examines direct taxes paid by the individuals, among which the largest share is occupied by personal income tax (hereinafter referred to as OIT). The study has found that the tax burden on the individuals is intensified by the introduced progressive scale of the PIT, increase in the minimum wage, in land tax rates, tax on their property, excises, introduction of a tourist tax, taxation of interest on bank deposits, etc. We have found a decrease in the social function of tax deductions for the PIT (standard, social, property ones), and budget losses due to their provision are insignificant. The introduced changes do not eliminate the existing differences in the level of salary of workers by industry and region.